NATO AND RUSSIAN POLITICAL POLICY ON EASTERN EUROPE - Napang, Marthen; Rohmann, Syaiful; Nurhasanah, Siti (UI Scholars Hub, 2020)
The growing centers of global power such as NATO, the European Union, China and India have different civilizational and cultural characteristics. Post-Soviet Russia is indeed in a relatively weak position in economic terms. Although Russia's relations with the European Union and the United States had improved after the Cold War, it did not have a significant impact on Russia's economic growth. In recent years Russia and other major powers have not only strengthened the economy and security related to the military, but have gone far beyond that to strengthen the country's influence. This is what makes the superpower countries compete in making policies that ultimately affect the world political and economic situation. This study examines Russian political policy towards NATO, Europe and Ukraine from the perspective of security and economic interests. The method used is qualitative by conducting an in-depth study of data obtained from the results of previous studies. The results of this study show that Russia, America and Europe through NATO occupy a strong position that has the ability to influence agreements and include the national interests of their country. Each country is trying to achieve their respective interests by making efforts to increase national power. National Power includes various elements, namely military power, economic and political power.